Kemampuan Fiskal Daerah Provinsi Jambi (Studi Hubungan Keuangan Pusat dan Daerah) - Devita, Andri; Handra , Hefrizal; Yonnedi , Efa (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to understand the main purpose of implementing regional autonomy is to improve public services and advance the regional economy in Jambi Province for the period 2000-2021. This research uses quantitative methods. The analytical method used is the regional financial ratio analysis method with the help of excel. The results of the study obtained that the amount of regional financial capacity through the average sum of the independence ratio, Effectiveness Ratio, Direct Expenditure Ratio, Indirect Expenditure Ratio and Expenditure Management Ratio on average during the period 2000-2021 was 71.92 percent including the category very good.